Translation Latin words in the text of the crop and farming (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article considers the peculiarities of using Latinisms in translating the texts on crop and agriculture, analyses the language resources and their influence on the meaning of lexical units. Special attention is paid to analyzing the Latin elements in lexical units and the ways of their realization in translation. The mechanisms of interaction of various factors in the borrowing of Latin origin tokens in different languages.
Keywords: Latinism; term; borrowing; agriculture; plant cultivation